1976
DOI: 10.1111/j.1432-1033.1976.tb11106.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Synthesis of Casein Messenger RNA during Pregnancy in the Rabbit

Abstract: The quantity of casein mRNA in the rabbit mammary gland was assayed during the course of pregnancy, by translation of casein mRNA in a reticulocyte lysate and by hybridization to DNA complementary to purified casein mRNA. Both methods indicated that the major increases in the concentration of casein mRNA in both polysomal and total cellular RNA occurred between the 18th and 25th day of pregnancy. The change in casein mRNA concentration during this period coincided with a sharp rise in casein synthesis in mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Our experiments revealed a significant increase in Wap expression, although significant variability was noted at the protein level. These results are in accordance with previous studies in the rabbit during pregnancy, showing that lactogenic hormones may function by increasing the rate of lactoprotein mRNA synthesis rather that initiating their transcription . Previous experiments in rodents had shown that dietary fatty acids prior to and during puberty altered the proliferative pathways in MEC and less frequently a few genes involved in the cell cycle pathway in adulthood .…”
Section: Discussionsupporting
confidence: 92%
“…Our experiments revealed a significant increase in Wap expression, although significant variability was noted at the protein level. These results are in accordance with previous studies in the rabbit during pregnancy, showing that lactogenic hormones may function by increasing the rate of lactoprotein mRNA synthesis rather that initiating their transcription . Previous experiments in rodents had shown that dietary fatty acids prior to and during puberty altered the proliferative pathways in MEC and less frequently a few genes involved in the cell cycle pathway in adulthood .…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown previously in mouse [33], rat [34], and rabbit [35] that the expression of milk protein genes starts in early to mid-pregnancy, increases throughout pregnancy and reaches a plateau in late pregnancy and early lactation. However, Finucane et al [12] found that milk protein genes did not show significant changes in expression from late pregnancy to early lactation but that protein expression of glucose transporter GLUT1 did increase.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the intensity of the blood flow might control the translation rate of casein mRNA by modulating the availability of metabolites involved in protein synthesis. This might explain why, during early pregnancy, most of the casein mRNA remains untranslated [64], while the mammary blood flow is limited. It is also conceivable that the intensity of milk synthesis during lactation is largely dependent upon mammary blood flow, which is itself controlled by prolactin, growth hormone [65], and oxytocin which controls the disengorgement of the mammary gland by milk withdrawal.…”
Section: Resultsmentioning
confidence: 99%